THE INFLUENCE OF KNOWLEDGE MANAGEMENT AND NON-PHYSICAL WORK-ENVIRONMENT ON BUSINESS PERFORMANCE OF TOFU PRODUCING MSMEs IN SUMEDANG - Aditya, Muhamad Sandy; Panigoro, Aggi; Saberina, Sabilla (Universitas Indonesia Membangun (Inaba), 2023)
The development of times and technology has driven the business ecosystem to become more dynamic. The ease of carrying out operations and business activities is a great opportunity for companies and entrepreneurs. A sustainable strategy is needed to ensure the long-term sustainability of business activities. The findings from this study are expected to determine whether there is influence of knowledge management, non-physical work environment, and organizational culture on business performance in the MSME industrial sector. From the results of this study, as for what the authors can conclude from several discussions, partially there is a significant influence and a very low relationship between Knowledge Management (X1) on Business Performance (Y), which is equal to 0.0650 or 6.5%, between Work Environment (X2) and Business Performance (Y), which is 0.0936 or 9.36%, between Organizational Culture (X3) and Business Performance (Y), which is 0.1705 or 17.05%. Simultaneously there is a significant influence and a strong relationship between Knowledge Management (X1), Non-Physical Work Environment (X2) and Organizational Culture (X3) on Business Performance (Y) with a contribution of 0.701 or 70.1%, and the rest has an influence other factors that can affect business performance is equal to 29.9%.